Need Analysis of 7E Instructional Model for Teaching Entrepreneurship Skills: A Case of Technical Colleges in Nigeria - Shuaibu, Halliru; Bin Kamin, Yusri; Ali Jogana, Musa; Bawa , Kabiru; Mukhtar, Nasiru (International Journal of Psychosocial Rehabilitation, 2020)
The advent of constructionism as a teaching approach in technical colleges curricula brought about the introduction of various teaching models in the colleges. For example, 5E and 7E begin to serve the application of the constructivist approach. However, technical teachers are an important factor in the teaching-learning process in Nigeria because the selection of the methodology of teaching largely depends on the teachers, based on the course content/material. The purpose of conducting this study is to explore the opinions of technical education specialists and teachers on the need for adopting the 7E instructional model in teaching entrepreneurship skills in technical colleges of Nigeria. Exploratory sequential mixed method design was employed in the study. 4 automobile teachers, 6 building teachers, 5 electrical installation and maintenance work teachers, and 5 metalwork teachers participated in the qualitative part of the study. A total of 20 participants were involved in the first phase of the study. In addition, the opinions of the trade teachers were obtained using semi-structured interviews and Atlas. It was used to transcribe information, code, and generate themes in the initial study. While 30 respondents answered the structured questionnaire in the second phase of the study, which is quantitative. Descriptive statistics is used for data analysis. Six technical colleges were used within the scope of the study. Based on the opinions of trade teachers, it has been concluded that the 7E instructional model is needed for teaching entrepreneurship skills in technical colleges in Nigeria.